The Quality of Screening Colonoscopies in an Office-Based Endoscopy Clinic - Douglas Bair; Joe Pham; M Bianca Seaton; Naveen Arya; Michelle Pryce; Trevor L Seaton (Canadian Journal of Gastroenterology)
BACKGROUND: Wait times for hospital screening colonoscopy have increased dramatically in recent years, resulting in an increase in patient referrals to office-based endoscopy clinics. There is no formal regulation of office endoscopy, and it has been suggested that the quality of service in some office locations may be inferior to hospital procedures.